APLIKASI METODE GEOLISTRIK RESISTIVITAS UNTUK ANALISIS BIDANG GELINCIR DAN STUDI KARAKTERISTIK LONGSORAN DI JALAN RAYA SUBAN BANDAR LAMPUNG - Rahmi Mulyasari; IG Boy Darmawan; Dersan Surya Effendi; Sugeng Purwo Saputro; Hesti Hesti; Akroma Hidayatika; Nandi Haerudin (Jurnal Geofisika Eksplorasi, 2020)
Pidada Urban Village, Panjang District, Bandar Lampung is an area that has medium to high landslide potential. One of landslides prone area triggered by rain located on Jalan Raya Suban. The slip surface areas under water-saturated soil is one of causes of landslides triggered by rain. Geophysical method used to detect slip surface is 2D Resistivity Method of Wenner-Schlumberger Configuration. In this study, an analysis of the slip surface has been carried out with the 2D resistivity method of the Wenner-Schlumberger Configuration and determination characteristic of landslide on Jalan Raya Suban. Based on the results of study indicated that the subsurface lithology consists of layers of tuff sediment, sandy clay and breccia. The slip surface is estimated at the boundary the layers of tuff sediment layer and sandy clay with depth (5-15) meters from the ground surface. The results of analysis and observation showed that type of landslide is translational fine-grained soil. Types of slope reinforcement that can be applied are civil and vegetative techniques.